ANALYSIS OF THE TRANSIENT STABILITY LIMIT OF NIGERIA’S 330kV TRANSMISSION SUB-NETWORK (Nigerian Journal of Technology, 2016)
The poor investment in the network expansion programme has led to high level of grid fragility experienced in the power transmission system in Nigeria. Thus, any little disturbance often results in cascaded outage which is very hazardous to the power system equipment and operation. In order to overcome or ameliorate the influence of this challenge, the network engineers have to devise methodologies based on the dynamic stability analysis. This motivates the development of power system transient stability model presented herein. The developed model is thus applied to a specimen of the Nigeria’s transmission power system, i.e. the Ikeja-West Sub-network. This choice is influenced by the fact that the Ikeja-West sub-network is the hub of power transmission arteries in Nigeria. Thus the Electrical Transient and Analysis Program (ETAP) software is deployed to operate on the ensuing model. This then leads to generating a series of results that demonstrates the different scenarios in respect of the system stability studies. The method adopted is quite appealing and promising as a tool in sustaining system stability and security during slight disturbance to the network during operation.http://dx.doi.org/10.4314/njt.v36i1.26